Solve the following simultaneous equations 7x - 6y =38 and 3x + 9y =-3

To solve these equations you first want to eliminate the same variable from each equation. In this question it is easiest to eliminate Y, to do this we will times equation 1 by 3 to get 21X-18Y=114 and equation 2 by 2 to get 6X+18Y=-6. Now, when you add both of or new equations together you get 27X= 108 which leads to X=4. We can now substitute X=4 into our 1st equation to find a value for Y. So, 7(4) -6Y= 38 implies that -6Y=10 hence Y=-5/3. To check your answer you can substitute X=4 and Y=-5/3 into the second equation to check the answer works, which it does.

Answered by Isabelle R. Maths tutor

2833 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

How would I simplify (3x^2 − 8x − 3)/(2x^2 −6x) fully?


When will I ever need to use this in real life?


Solve x^2+6x-7 by completing the square.


How do I know when to use SOHCAHTOA and when to use the sine or cosine rule?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences